Implementasi UU no 8 tahun 1999 mengenai perlindungan hak konsumen: Hukum islam - Muniru, Hiththatun Zamrud Madu Kirana Al Badru (Maliki Interdisciplinary Journal, 2024)
The state has a role to protect, respect, fulfill, and promote the human rights of consumers. Not a few consumer complaints sent to the National Consumer Protection Agency (BPKN) show that consumer protection is currently ineffective and weak. This is due to inadequate laws to protect consumers, so the country's constitution must be strengthened. Law Number 8 of 1999 is a special law that regulates consumer protection. The issue raised in this study is how to protect consumer rights according to Islamic law and Law No. 8 of 1999. The implementation of the Consumer Protection Law (UUPK) shows the Government's responsibility in protecting consumers, business entities, and other parties. This research is descriptive and this type of research is legally normative because there are value and principle of consumer protection in Islam that must be practiced by Muslims today.